Treatment of carpet and metallic effluents by China clay - Gupta G.S.; Singh A.K.; Tyagi B.S.; Prasad G.; Singh V.N. (My University, 2025)
This paper addresses the treatment of carpet and metallic effluents containing some popular chrome dyes, i.e. Omega Chrome Red ME (CI 18735), Metomega Chrome Orange GL and Omega Chrome Fast Blue B (C.I. 16680) and heavy metals, i.e. iron, zinc and manganese by adsorption on china clay. China clay exhibits a good affinity for Metomega Chrome Orange GL and zinc, significant uptake of Omega Chrome Red ME, manganese and iron but a poor scavenger for Omega Chrome Fast Blue B. High removal of the above pollutants has been noted at low initial concentration. The process of uptake follows a first order adsorption rate expression and obeys Langmuir's model of adsorption. The removal process has also been found to be partially diffusion controlled and mass transfer coefficients have been determined to explain the results. The effect of temperature on the removal of adsorbates has also been studied. Acidic pH has been found to be more effective in the case of dyes and iron while in the case of zinc and manganese a basic pH around 8·0 has showed appreciable results. The effect of pH has been discussed incorporating various surface site reactions. Copyright © 1992 Society of Chemical Industry